Impact of Gender, Age, and Education of Peer-to-Peer Lender on Loan Viability Assessment: Evidence from Sharia Firm - Maulia, Azzahra; Gultom, Yohanna M.L. (The Indonesian Capital Market Review, 2023)
Peer-to-peer (P2P) lending offers investors the discretion to allocate funds based on their risk toler- ance. However, funds cannot be withdrawn until loans mature or are repaid by borrowers, rendering it a relatively high-risk investment. Research suggests that women in older age groups tend to exhibit greater risk aversion, though financial literacy may mitigate gender disparities. This study employs logistic regression to analyze the impact of gender, age, and education on P2P loan viability assess- ment. Our findings indicate that, generally, older lenders are less likely to finance high-risk loans. However, older women with at least a bachelor’s degree display behaviors that contradict this theory.